The Chechen wars : will Russia go the way of the Soviet Union? - Evangelista, Matthew, 1958- (Brookings Institution Press, 2002)
Russian presidents Yeltsin and Putin justified their invasions of Chechnya as necessary to prevent a breakup of the Russian Federation. Evangelista challenges these justifications by exploring the sources of both wars and the implications for Russia's internal coherence and international standing.